Differences in priorities assigned to patients by triage nurses and by consultant physicians in accident and emergency departments. Issue 4 (August 1993) - George, S; Read, S; Westlake, L; Fraser-Moodie, A; Pritty, P; Williams, B
Abstract : STUDY OBJECTIVES--To investigate whether the greater urgency assigned to accident and emergency patients by triage nurses than by accident and emergency doctors was uniform across all patient groups. DESIGN--Patients attending an accident and emergency department between 8.00 am and 9.00 pm over a six week period were assessed prospectively for degree of urgency by triage nurses, and retrospectively for urgency by one of two consultant accident and emergency doctors. Patients were grouped according to their clinical mode of presentation. SETTING--An accident and emergency department of a district general hospital in the Midlands, UK, in 1990. PATIENTS--1213 patients who presented over six weeks. MEASUREMENTS AND MAIN RESULTS--As might be expected, patients' conditions were assessed as being more urgent prospectively than retrospectively. This finding, however, was not uniform across all patient groups. Nurses' assessments of urgency tended to favour children and patients who presented with eye complaints and gave less priority to medical cases, particularly those with cardiorespiratory symptoms. CONCLUSIONS--These findings have implications for all those involved in the organisation of triage systems and in the training of nurses in accident and emergency departments. It is essential that judgements on how urgently patients need to be seen are made in a completely objective manner.